EGFR-dependent TOR-independent endocycles support Drosophila gut epithelial regeneration - Jinyi Xiang (Nature Portfolio, 2017)
In response to gut epithelial damage,Drosophilastem cells proliferate to produce large polyploid enterocytes (EC), which comprise the bulk of the epithelium. Here, the authors show that stress-dependent EGFR/MAP kinase signalling drives both endoreplication and cell growth in newborn ECs.